2013
DOI: 10.1186/1475-2891-12-149
|View full text |Cite
|
Sign up to set email alerts
|

Diet and toenail arsenic concentrations in a New Hampshire population with arsenic-containing water

Abstract: BackgroundLimited data exist on the contribution of dietary sources of arsenic to an individual’s total exposure, particularly in populations with exposure via drinking water. Here, the association between diet and toenail arsenic concentrations (a long-term biomarker of exposure) was evaluated for individuals with measured household tap water arsenic. Foods known to be high in arsenic, including rice and seafood, were of particular interest.MethodsAssociations between toenail arsenic and consumption of 120 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 71 publications
4
32
2
Order By: Relevance
“…S2), which signifies that hair and nail samples are effective biomarkers for As exposure . The data in Table 3 depict that our nail samples have lower and/or similar As levels than those reported from Bangladesh (Rahman et al, 2001;Rakib et al, 2013) and India (Samanta et al, 2004;Sanz et al, 2007;Rahman et al, 2001), but far higher than another study from Pakistan (Anwar, 2005), USA (Cottingham et al, 2013;Karagas et al, 2001) and Japan (Tabata et al, 2006). Since hair and nails have similar chemical nature, it can be expected that they would have similar As accumulation trends and patterns throughout the world.…”
Section: As Levels In Nail Samplessupporting
confidence: 48%
See 1 more Smart Citation
“…S2), which signifies that hair and nail samples are effective biomarkers for As exposure . The data in Table 3 depict that our nail samples have lower and/or similar As levels than those reported from Bangladesh (Rahman et al, 2001;Rakib et al, 2013) and India (Samanta et al, 2004;Sanz et al, 2007;Rahman et al, 2001), but far higher than another study from Pakistan (Anwar, 2005), USA (Cottingham et al, 2013;Karagas et al, 2001) and Japan (Tabata et al, 2006). Since hair and nails have similar chemical nature, it can be expected that they would have similar As accumulation trends and patterns throughout the world.…”
Section: As Levels In Nail Samplessupporting
confidence: 48%
“…Nevertheless, several studies have reported As levels in hair and nail along with water and soil of different areas (Tsuji et al, 2005;Chiou et al, 1997;Lin et al, 1998) but very few studies has reported their association with dust and air particles (Huang et al, 2014;Tsuji et al, 2005). Similarly, a number of studies have reported As concentrations in human nail and hair, and reported them as an effective bio-monitoring tool for As exposure (Cottingham et al, 2013;Rakib et al, 2013;Samanta et al, 2004;Sanz et al, 2007;Anwar, 2005), due to their keratin tissue composition, containing high cystein residues that have affinity for diverse metals transported via body fluids, thus become part of these metabolic inactive tissues (Tsuji et al, 2005 andHuang et al, 2014). Hence, once As is accumulated into these non-invasive tissues, can easily be collected and used to monitor past As exposure into human body (Gualt et al, 2008;Hinwood et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Within the NHBCS, total urinary arsenic and toenail arsenic concentrations have been shown previously to correlate with the arsenic concentration of household drinking water 21, 22 , and with the consumption of certain dietary items known to contain elevated concentrations of arsenic 17, 19, 20 . The arsenic biomarkers reported in this study, in addition to placenta, mirror previous findings.…”
Section: Discussionmentioning
confidence: 92%
“…17,18 Maternal toenails underwent an additional washing procedure that included manual removal of visible dirt and five washes in an ultrasonic bath using Triton X-100 (LabChem Inc., PA) and acetone followed by deionized water, and allowed to dry. All toenail samples were subject to low-pressure microwave digestion using the method outlined above for placenta digestions and were analyzed via ICP-MS.…”
Section: Methodsmentioning
confidence: 99%
“…A recent case–control study in New Hampshire found positive relationship between urinary arsenic metabolites and SCC incidence in humans [94]. Another investigation observed that dietary arsenic from atypical sources such as dark meat fish (e.g., tuna steaks, mackerel, salmon, sardines, bluefish, and swordfish) correlated closely with toenail arsenic concentrations, a common marker for arsenic exposure [95]. Further investigation in a population-based case–control study by the same group supported the finding that demonstrated a positive relationship between the consumption of long chain fatty acids, typically found in fish oils, and toenail arsenic.…”
Section: Discussionmentioning
confidence: 99%